Analysis of the Possibilities for Establishing an International Rail Corridor in the Context of Ongoing and Planned Linear Investments Along Its Route - Jacek Rutkowski; Jarosław Kiepura (Przegląd Komunikacyjny)
Abstract: The key condition for the implementation of the Three Seas Initiative, is the creation of a modern transport network with infrastructure along the north-south axis - one which integrates the economies of the countries included in this area and creates favorable conditions for the development of economic cooperation. This applies in particular to rail and cross-border connections, which - in order to achieve the standards of connections on the east- west axis - require huge investments and construction of new routes that could enable the process of railway network integration across the Three Seas region. This paper focuses on outlining the assumptions for the construction of the route with the working name "Rail Adriatica", which is an alternative variant (shifted to the east) of the RFC 11 Amber corridor. The aim of the proposed investment is the creation of a route, which would consist of four railway corridors with high operational parameters (construction of new sections along with modernization and revitalization of existing sections), that would connect the most economically productive areas of the Three Seas countries, including Poland, the Czech Republic, Slovakia, Hungary, Slovenia, Croatia and northeast Italy. The route would by design connect these areas with the main Adriatic and Baltic ports of the Three Seas Initiative, creating new revenue streams for the entire region.